Gene X Two Triple Mutations Predominance on Chronic Hepatitis B Virus in Padang, West Sumatra Indonesia - Afida Razuna Ave; Andani Eka Putra; Saptino Miro (The Indonesian Society for Digestive Endoscopy, 2022)
Background: Hepatitis B is a health issue that become major problem worldwide with high morbidity. Hepatitis B is a liver infection that caused by Hepatitis B Virus. Chronic hepatitis B is a liver inflammation that lasted more than 6 months and it has the potential to progress to liver cirrhosis and hepatocellular cancer. The disease is influenced by Gene X and viral genotype. Mutations in the Gene X are suspected to having a role in disease progression. The aim of this study was to detect Gene X polymorphism and the phylogeny of HBV from Padang local clinical samples of chronic hepatitis B (CHB), West Sumatera, Indonesia.Method: The entire chronically HBV-infected patients were enrolled in this study: 38 CHB. The research samples were the entire Hepatitis B serum from Indonesian Red Cross Blood Bank than Gene X was amplified using nested PCR, which produced two fragments and aligned with X sequence database continued with mutation analysis. Results: In this study we found all the samples were having nucleotide variation. Of various mutations, we observed the presence of known liver cirrhosis and HCC-related HBx protein mutant i.e double mutations (HBx130 and HBx131) and two triple mutations (HBx5/HBx130/HBx131) and (HBx127/HBx130/HBx131) were high. The analysis also showed that patients were infected mainly by genotype C at 72,2% and followed by B at 27,8%.Conclusion: We conclude that all the samples have nucleotide variation and the mutation implying that molecular progression between the virus and the host at chronically infected patients.